Women as Patrons and Benefactors of the Mendicant Friars in Medieval Connacht - McDermott, Yvonne (Journal of Medieval Monastic Studies, 2019)
Abstract This article considers the nature and variety of forms of patronage bestowed by women on friaries in Connacht in the west of Ireland in the high and late medieval period. Two detailed case studies are presented to this end. The first deals with the evidence for Athenry Dominican priory, drawing especially on the priory’s register, a survival of a type rare for medieval Ireland. The second considers Creevelea Franciscan friary, a foundation attributed to a Gaelic-Irish woman. The contrasts between the types of patronage provided by women and men are drawn out as are the differences between Anglo-Irish and Gaelic-Irish women, in terms of their capacity to act as patrons and the forms taken by their beneficence. The motivations of female patrons are considered.